Risk of post-pregnancy hypertension in women with a history of hypertensive disorders of pregnancy: nationwide cohort study. (12th July 2017) - Behrens, Ida; Basit, Saima; Melbye, Mads; Lykke, Jacob A; Wohlfahrt, Jan; Bundgaard, Henning; Thilaganathan, Baskaran; Boyd, Heather A
Abstract : Objectives  To determine how soon after delivery the risk of post-pregnancy hypertension increases in women with hypertensive disorders of pregnancy and how the risk evolves over time. Design  Nationwide register based cohort study. Setting  Denmark. Populations  482 972 primiparous women with a first live birth or stillbirth between 1995 and 2012 (cumulative incidence analyses), and 1 025 118 women with at least one live birth or stillbirth between 1978 and 2012 (Cox regression analyses). Main outcome measures  10 year cumulative incidences of post-pregnancy hypertension requiring treatment with prescription drugs, and hazard ratios estimated using Cox regression. Results  Of women with a hypertensive disorder of pregnancy in a first pregnancy in their 20s, 14% developed hypertension in the first decade post partum, compared with 4% of women with normotensive first pregnancies in their 20s. The corresponding percentages for women with a first pregnancy in their 40s were 32% and 11%, respectively. In the year after delivery, women with a hypertensive disorder of pregnancy had 12-fold to 25-fold higher rates of hypertension than did women with a normotensive pregnancy. Rates in women with a hypertensive disorder of pregnancy were threefold to 10-fold higher 1-10 years post partum and remained twice as high even 20 or more years later. Conclusions  The risk of hypertension associated with hypertensive disorders of pregnancy is high immediately after an affected pregnancy and persists for more than 20 years. Up to one third of women with a hypertensive disorder of pregnancy may develop hypertension within a decade of an affected pregnancy, indicating that cardiovascular disease prevention in these women should include blood pressure monitoring initiated soon after pregnancy.